Analyzing the Effectiveness of Laser and Pneumatic Lithotripsy in the Treatment of Ureteral Stones Smaller than 1.05 Centimetres in Diameter a Multi-Center Study - Muhammad Shahzad, Farhat Ullah Khan, Azra A Ghani, Fazli Wahab, Zafar Ahmad Khan, Alina Akram (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: aims to compare the success rates of laser lithotripsy with pneumatic lithotripsy for removing ureteric stones less than 1.5 cm at a tertiary care hospital. Method: This Multi-Center study was conducted in the urology department of Lady Reading Hospital in Peshawar total of 265 patients (125 in the PL group and 140 in the LL category) with ureteral stones were treated with ureteroscopic lithotripsy. The study’s authors aimed to compare factors such as rates of stone-free patients, operation length, patient recovery time, length of hospital stay, stone migration, and complication rates. Results: Age distribution, gender distribution, typical stone size, stone point, and level of complexity were all comparable between the two groups. The LL group stood out from the rest regarding stone repositioning, SFR, and MHS. Conclusion: The [PL and LL] methods worked well and were safe for ureteral stones. However, the [LL] group may have had a greater SFR. Keywords: comparing, pneumatic lithotripsy, ureteral stones